## Using trig identities, prove the equation shown below. sec(x) – sin(x)tan(x) = cosx Hint: Work on the left side

Question

Lost your password? Please enter your email address. You will receive a link and will create a new password via email.

## Answers ( )

Answer:

Step-by-step explanation:

Prove that

sec(x) – sin(x)tan(x)=cosx

sec(x)=1/cos(x) tan(x)=sin(x)/cos(x)

1/cos(x) – sin(x) x sin(x)/cos(x)

(1-sin(x) x sin(x))/cos(x)

(1-sin^2(x))/cos(x) 1-sin^2(x)=cos^2(x)

Cos^2(x)/cos(x)

(Cos(x) x cos(x))/cos(x)

cos(x) proved